Truth, beauty, and goodness in biblical narratives : a hermeneutical study of Genesis 21:1-21 - Sonek, Krzysztof (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft ;, 2009)
A modern reader studying biblical narratives encounters various literary approaches and ways of understanding interpretive concepts. Hence an attempt to put forward a comprehensive hermeneutical model of reading biblical narratives. Such a model should aim at a synthesis of various approaches, and show how they are interrelated. The book proposes a hermeneutical theory which uses modern approaches to literary texts for the exegesis of biblical narratives. The book discusses three spheres of the reader's knowledge about reality: immanent, narrative, and transcendental. The move from immanent to.